2013
DOI: 10.1016/j.jyp.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and evaluation of N-mannich bases of 2-substituted Benzimidazole derivatives

Abstract: a b s t r a c tRationale: Benzimidazoles and its derivatives represent one of the mainly biological active classes of literature. Aim: In this present study aimed to synthesize N-mannich bases derivatives compounds bearing of 2-substituted benzimidazole moiety, in order to investigate their possible biological activity. Method: Benzimidazole compounds were prepared from the condensation reaction between ortho phenylene diamine and various acids. Mannich base of newly synthesized Benzimidazole derivatives were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The origin of the special interest towards benzimidazole derivatives has been the 5,6-dimethyl-1-(α- d -ribofuranosyl)-benzimidazole structure, which is a basic part of vitamin B12 [ 8 ]. Furthermore, the benzimidazole ring is a structural bioisostere of some of the nucleobases existing in natural nucleotides, which can interact easily with the biopolymers in living systems [ 9 ]; this feature is often accepted as the responsible for its biological importance, either alone or as incorporated into different templates. It has been reported to show many pharmacological activities including antimicrobial, MAO or cyclooxygenase (COX) inhibitory, or anticholinesterase [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the special interest towards benzimidazole derivatives has been the 5,6-dimethyl-1-(α- d -ribofuranosyl)-benzimidazole structure, which is a basic part of vitamin B12 [ 8 ]. Furthermore, the benzimidazole ring is a structural bioisostere of some of the nucleobases existing in natural nucleotides, which can interact easily with the biopolymers in living systems [ 9 ]; this feature is often accepted as the responsible for its biological importance, either alone or as incorporated into different templates. It has been reported to show many pharmacological activities including antimicrobial, MAO or cyclooxygenase (COX) inhibitory, or anticholinesterase [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluconazole and ampicillin were utilized as reference drugs for antifungal and antibacterial study respectively. The analogues 4(a) and 4(b) were found to be more efficient and potent among other derivatives (12).…”
Section: Antimicrobial Activitymentioning
confidence: 94%
“…Another series of mannich base of N-(benzimidazol-1-yl methyl)-4-chlorobenzamide analogues (2) were prepared and characterized for antimicrobial action against various bacterial strains like S. aureus, B. subtilis, E. coli and P. aeruginosa along with fungal strains, C. albicans and A. niger. Amongst various synthesized derivatives some compounds showed effective antimicrobial activity (12).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…17) A series of mannich bases of benzimidazole derivatives were synthesized from o-phenylenediaamine in two steps via benzimidazole intermediates. The anti fungal and anti bacterial activities of synthesized compounds 3a-c (18,19,20) were also checked andit was found that compounds 3a, 3b and 3c showed excellent antibacterial activity and compound 3a showed good antifungal activity than others (Aanadhi et al, 2013). …”
Section: )mentioning
confidence: 99%